Evaluation of social skills of the upper class secondary school students - Greychene I. V., Shniras S. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
it is specified in the article that a lack of situational social skills in daily life situations imply a significant problem for school-age students. Therefore, this paper is intended to evaluate how situational social skills of upper class secondary school students are evaluated.
Keywords: студенты; коммуникативные навыки; девушки; students; girls; boys; social skills; парни